OP116 Cost-Effectiveness Of Sacubitril/Valsartan In Heart Failure. (2017) - Lin, Liang; Aziz, Mohamed Ismail Abdul; Wu, David Bin-Chia; Ng, Kwong
Abstract : INTRODUCTION: Heart failure (HF) is a major public health problem worldwide and in Asia. Sacubitril/valsartan reduces cardiovascular death and hospitalizations for HF. However, decision makers need to determine whether its benefits are worth the additional costs, given the low-cost generic status of current standard of care. METHODS: Using a Markov model, we projected lifetime clinical and economic outcomes of sacubitril/valsartan versus enalapril for 66-year-old patients with HF in Singapore. Key health states included New York Heart Association (NYHA) classes; patients in each state incurred a monthly risk of hospitalization for HF and cardiovascular death. Probabilities of events were based on the PARADIGM-HF trial. The uncertain treatment effect of sacubtril/valsartan in Asian patients was modelled using a hazard ratio (HR) of 1 as upper limit in sensitivity analyses. Utilities were obtained from published literature. Local national epidemiological and cost data were applied. Analyses were conducted from the Singapore healthcare payer's perspective. Both one-way and Probabilistic Sensitivity Analyses (PSA) based on 10, 000 Monte Carlo simulations were performed. RESULTS: Compared to enalapril, sacubitril/valsartan was associated with an incremental cost-effectiveness ratio (ICER) of SGD74k (USD52k) per quality-adjusted life year (QALY) gained. The cost-effectiveness of sacubitril/valsartan was highly dependent on its effectiveness in reducing the risk of cardiovascular death. However, this was uncertain, particularly in the Asian subgroup, where results were not statistically significant. In sensitivity analyses using results from Asian patients, the ICERs ranged from SGD41k (USD30k) to SGD1.3 million (USD 0.94 million) per QALY gained. PSA showed the probability of sacubitril/valsartan being cost-effective was below 1 percent, 12 percent and 71 percent at thresholds of SGD20k (USD14k), SGD50k (USD36k) and SGD100k (USD 72k) per QALY gained, respectively. CONCLUSIONS: Given the uncertain ICER, sacubtril/valsartan may not provide good value for money compared to enalapril in reducing cardiovascular morbidity and mortality in patients with HF at the current daily cost. Our study highlights the cost-benefit trade-off that healthcare professionals and patients face when considering HF therapy.